Synthesis and Characterization of Dioxotungsten(VI) Complexes of Azodyes Derived from 1-Phenyl-2,3-dimethyl-4-Amino-5-Pyrazolone - Harikumaran Nair, M.L.; Kumari Nisha, K.R. (Asian Journal of Chemistry, 2016)
Some novel dioxotungsten(VI) complexes of general formula [WO2LXCl] (X = Cl, NO3, NCS or ClO4 and L = 1-phenyl-2,3-dimethyl-4-(2-hydroxy naphthylazo)-5-pyrazolone or 1-phenyl-2,3-dimethyl-4-(2,4-dihydroxy phenylazo)-5-pyrazolone have been synthesized and characterized by elemental analysis, IR and NMR spectral studies. The thermal behaviour of one of the complexes has also been examined. Ligands and their few metal complexes were screened for their antibacterial activities against gram positive and gram negative bacteria. The molar conductance values of the complexes indicate that the complexes are non-electrolytes.